Competitiveness and Growth in Brazilian Cities : Local Policies and Actions for Innovation - Zhang, Ming (World Bank, 2012)
Given the Brazilian federal government's high priority on economic growth, competitiveness is at the top of the economic agenda. While economic policies at the national level are important to this agenda, more than 75 percent of people live in urban areas, which produce more than 90 percent of the gross domestic product (GDP). 'What can cities do to improve economic performance and create jobs?' Mayors, governors, and federal government officials have frequently asked this question. For cities, economic competition has become more intense with globalization. Many municipal officials have been striving to enhance municipal infrastructure and services, while others have also been working on reducing the cost of doing businesses to make their areas more attractive for private investment. On the other hand, promoting local economic growth without considering local context and market conditions does not always achieve expectations. The policies discussed in this report are essentially about promoting local economic development. However, the author believe that the term competitiveness, as a dynamic concept, is helpful for local policy makers as it implies two essential aspects of promoting local economic development in today's environment: (a) cities not only need to provide a good business environment, they need to strive to provide a better one than others, at least in certain aspects (or niches); and (b) cities need to continually upgrade and innovate to achieve sustained growth.